A bibliometric assessment of energy research in South Africa - Pouris, Anastassios (South African Journal of Science, 2016)
The results of an effort to identify the performance of energy and fuels research in South Africa during the most recent period (2003–2013) are reported. Bibliometric approaches have been employed in order to assess the field of energy research. Energy research was identified to be improving over time, albeit from a small basis. The field appears to equally emphasise fossil and renewable energy research. Similarly, universities were identified to be producing a subcritical number of energy articles in comparison with international organisations. The relatively small activity in the energy field appears to affect the international collaboration of the field, which is well below the national average. International comparisons in terms of articles per GWH of electricity produced and articles per million population show that South Africa should increase substantially its effort in the field in order to be comparable with other countries. Significance: • This article makes a unique contribution in scientometrics to the field of energy research in South Africa which, given its multidisciplinary nature, is a generally neglected field of study in South Africa.